Incentives for corporate tax planning and reporting: Empirical evidence from Australia - Taylor, Grantley; Richardson, G. (Elsevier Ltd, 2014)
This study extends prior research on the willingness of firms to significantly decrease their corporate taxes. It specifically examines the associations between corporate tax avoidance and the reported significant uncertainty of a firm’s tax position, the tax expertise and tax affiliations of its directors, and the performance-based remuneration incentives of its key management personnel. Based on a dataset of 200 publicly listed Australian firms over the 2006–2010 period (1000 firm years), we find that the reported uncertainty of a firm’s tax position, the tax expertise of its directors, and the performance-based remuneration incentives of its key management personnel are significantly positively associated with tax avoidance. Conversely, firms with board members who have at least one tax-related affiliation are significantly negatively associated with tax avoidance.